2‐Hydroxybenzophenone as a Chemical Auxiliary for the Activation of Ketiminoesters for Highly Enantioselective Addition to Nitroalkenes under Bifunctional Catalysis. Issue 19 (14th April 2018) - Guerrero‐Corella, Andrea; Esteban, Francisco; Iniesta, Manuel; Martín‐Somer, Ana; Parra, Mario; Díaz‐Tendero, Sergio; Fraile, Alberto; Alemán, Jose
Abstract: An organocatalytic system is presented for the Michael addition of monoactivated glycine ketimine ylides with a bifunctional catalyst. The ketimine bears an ortho hydroxy group, which increases the acidity of the methylene hydrogen atoms and enhances the reactivity, thus allowing the synthesis of a large variety of α, γ‐diamino acid derivatives with excellent stereoselectivity. Abstract : Groomed for success : An organocatalytic system was developed for the Michael addition of azomethine ylides with a single activating group. To increase the acidity of the methylene hydrogen atoms and enhance the reactivity of the system, ketimine substrates with an ortho hydroxy group were formed. This approach enabled the synthesis of a large variety of α, γ‐diamino acid derivatives with excellent stereoselectivity.